Strain method for doubly reinforced rectangular beams design - Prieto-Serrano, Luis Rafael (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The compressed steel in a doubly reinforced beam improves ductility, reduces immediate and long-term deflections, it is available to support the tension in sections under reversal stress, and in low-height beams, it increases strength. With the expected strain as a measure of the section ductility, the paper proposes a direct methodology to determine the necessary compression quantities and tension reinforcement. It finds that the most efficient sections are those for which the tension reinforcing strain is 0.005.